2021
DOI: 10.1186/s13062-020-00288-x
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble learning approach for modeling the systems biology of drug-induced injury

Abstract: Background Drug-induced liver injury (DILI) is an adverse reaction caused by the intake of drugs of common use that produces liver damage. The impact of DILI is estimated to affect around 20 in 100,000 inhabitants worldwide each year. Despite being one of the main causes of liver failure, the pathophysiology and mechanisms of DILI are poorly understood. In the present study, we developed an ensemble learning approach based on different features (CMap gene expression, chemical structures, drug t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The DILI classifications for this challenge also changed from binary to a most, less, ambiguous, and no-DILI concern which is in line with the FDA DILIrank dataset. Predictive model rates from multiple distinct approaches to this challenge in 2019 often yielded similar accuracy results around 0.70 (Aguirre-Plans et al, 2021;Lesiński et al, 2021;Liu et al, 2021). While it is difficult to make a direct comparison across the years of these challenges considering how the fundamental elements of predictive modeling, such as the data sources and classifications, have changed, the goal of the challenge has remained the same in modeling the risk of a drug to lead to liver injury in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DILI classifications for this challenge also changed from binary to a most, less, ambiguous, and no-DILI concern which is in line with the FDA DILIrank dataset. Predictive model rates from multiple distinct approaches to this challenge in 2019 often yielded similar accuracy results around 0.70 (Aguirre-Plans et al, 2021;Lesiński et al, 2021;Liu et al, 2021). While it is difficult to make a direct comparison across the years of these challenges considering how the fundamental elements of predictive modeling, such as the data sources and classifications, have changed, the goal of the challenge has remained the same in modeling the risk of a drug to lead to liver injury in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This approach produced models with an accuracy of 75.9% that were also able to correctly identify targets associated with the mechanism of action and toxicity of nonsteroidal antiinflammatory drugs, a class of drugs commonly associated with DILI. Aguirre et al utilized the widest array of predictive data, including L1000 CMap expression, drug-target associations, structural data, phenotype-associated gene signatures, proteinprotein interactions, and drug targets data (Aguirre-Plans et al, 2021). Their models' accuracy remained comparable to other study results at 70%, but they also identified structural dissimilarities within the DILI risk labels used.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of AGPs will be further improved through the use of special dedicated software [174], detection of PNAs using nanopore platforms [175], and with rational improvements in reducing side effects such as hepatotoxicity [176]. Machine learning algorithms partially help alleviate this problem by predicting possible side effects of experimental drugs, however, a lot of work needs to be done in this direction [177][178][179] In terms of exciting perspectives that may open sometimes for oncological applications of AGPs, arming of oncolytic viruses with transgenes encoding AGP-synthesizing polymerases inside the cancer cells would be of great interest, since such an approach may greatly boost the action of cytotoxic drugs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The Graph neural network has been proved to be the most advanced model in many fields, such as molecular attribute prediction [ 13 , 14 ] and has also achieved high prediction accuracy in DILI prediction [ 15 , 16 ]. At the same time, ML models based on toxicogenomics have also achieved high accuracy [ 2 ]; however, their accuracy is highly dependent on experimental data, and the experimental accuracy on large datasets is not satisfactory (the best-obtained accuracy is 0.7) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%